Tranformasi Manajemen Sumber Daya Manusia Pendidikan Sekolah Menengah Atas Dalam Penerapan Kurikulum Merdeka - Achmadi, Achmadi; Muhammad Basri; Muhammad Rifai Irfan (Journal Pendidikan Ilmu Pengetahuan Sosial, 2025)
The implementation of the Merdeka Curriculum demands a fundamental paradigm shift in human resource management (HRM) within Senior High Schools. This study aims to analyze the transformation of educational HRM, specifically focusing on strategies to enhance teacher competence and adapt to the digital demands of the new curriculum. Employing a descriptive qualitative approach, this research maps the dynamics of HR governance in navigating policy changes. The results indicate that schools are shifting from rigid administrative management to more adaptive and flexible approaches. Key transformation strategies identified include the transition to bottom-up professional development, the utilization of the Merdeka Mengajar Platform (PMM) for data-driven supervision, and the alignment of teacher organizational culture with the Pancasila Student Profile. The study concludes that effective HRM transformation is crucial for creating a responsive educational ecosystem and supporting teachers' evolution from mere curriculum executors to innovative learning designers. These findings offer practical insights for school leaders in managing workforce agility amidst educational reforms